2022
DOI: 10.1177/00332941221080410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Mindfulness-Based Intervention on Self-Compassionate Behaviors: A Randomized Controlled Trial

Abstract: Self-compassion is regarded as a mediating or moderating variable in mindfulness-based interventions (MBI). However, few studies have investigated the role of self-compassion on MBI. Therefore, we conducted a randomized controlled trial to examine whether (1) MBI decreases depression and trait anxiety, while increasing trait mindfulness, trait self-compassion, self-compassionate behaviors (SC behaviors), and behaviors, along with improving mood; and (2) SC behaviors moderate the effect of mindful behaviors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated an association between improved self-compassion and reduced negative emotion ( 16 , 17 , 22 26 ). Self-compassion is regarded as a mediating or moderating variable in MBIs ( 19 , 27 ). Nonetheless, a systematic review failed to identify this relationship ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated an association between improved self-compassion and reduced negative emotion ( 16 , 17 , 22 26 ). Self-compassion is regarded as a mediating or moderating variable in MBIs ( 19 , 27 ). Nonetheless, a systematic review failed to identify this relationship ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chin et al (2021) found that both the standard 8-week MBSR training program, and a modified 8-week MBSR-adapted training program that focused on monitoring skills, improved momentary (and trait measures) of attention control. In another study, Uchida et al (2022) tested the effects of an 8-week standard mindfulness intervention in a sample of 19 patients with depression and/or anxiety. Although no significant changes in mental health were observed, results revealed significant improvements in self-compassionate and mindful behaviors.…”
mentioning
confidence: 99%